x = 1 + 2t
y = 2 - 3t
z = -5 + t
Also, we know that:
2x + 5y - 3z = 6
Substituting for x, y and z in the that equation gives:
2 * (1 + 2t ) + 5 * ( 2 - 3t ) - 3 * ( -5 + t ) = 6
2 + 4t + 10 - 15t + 15 - 3t = 6
4t - 15t - 3t = 6 - 2 - 10 - 15
- 14t = - 21 Divide both sides with -14
t = - 21 / -14
t = ( 7 * 3 ) / ( 7 * 2 )
t = 3 / 2
x = 1 - t
x = 2 / 2 - 3 / 2
x = - 1 / 2
y = 3 t
y = 3 * 3 / 2
y = 9 / 2
Find the point in which the line x=1-t, y=3t, z=1+t; meet the plane 2x-y+3z=6
2 answers
x = 1 + 2t
y = 2 - 3t
z = -5 + t
Also, we know that:
2x + 5y - 3z = 6
Substituting for x, y and z in the that equation gives:
2 * (1 + 2t ) + 5 * ( 2 - 3t ) - 3 * ( -5 + t ) = 6
2 + 4t + 10 - 15t + 15 - 3t = 6
4t - 15t - 3t = 6 - 2 - 10 - 15
- 14t = - 21 Divide both sides with -14
t = - 21 / -14
t = ( 7 * 3 ) / ( 7 * 2 )
t = 3 / 2
x = 1 - t
x = 2 / 2 - 3 / 2
x = - 1 / 2
y = 3 t
y = 3 * 3 / 2
y = 9 / 2
z = 1 + t
z = 2 / 2 + 3 / 2
z = 5 / 2
Coordinate of point:
( - 1 / 2 , 9 / 2 , 5 / 2 )
y = 2 - 3t
z = -5 + t
Also, we know that:
2x + 5y - 3z = 6
Substituting for x, y and z in the that equation gives:
2 * (1 + 2t ) + 5 * ( 2 - 3t ) - 3 * ( -5 + t ) = 6
2 + 4t + 10 - 15t + 15 - 3t = 6
4t - 15t - 3t = 6 - 2 - 10 - 15
- 14t = - 21 Divide both sides with -14
t = - 21 / -14
t = ( 7 * 3 ) / ( 7 * 2 )
t = 3 / 2
x = 1 - t
x = 2 / 2 - 3 / 2
x = - 1 / 2
y = 3 t
y = 3 * 3 / 2
y = 9 / 2
z = 1 + t
z = 2 / 2 + 3 / 2
z = 5 / 2
Coordinate of point:
( - 1 / 2 , 9 / 2 , 5 / 2 )